P090 Unraveling the rewiring of cytokine signalling in Inflammatory Bowel Disease using a novel network biology approach. (21st January 2022) - Olbei, M; Thomas, J; Hautefort, I; Treveil, A; Bohar, B; Madgwick, M; Gul, L; Csabai, L; Modos, D; Korcsmaros, T
Abstract: Background: Intercellular communication mediated by cytokines is critical to the development of immune responses, particularly in the context of chronic immune-mediated disorders such as inflammatory bowel disease (IBD). By releasing these small molecular weight peptides, the source cells can influence numerous intracellular processes in the target cells, including the secretion of other cytokines downstream. However, there are no readily available resources and studies modelling cytokine-cytokine interactions that would be important for better understanding the dysregulation of cytokine signalling in IBD, and revealing potential new therapeutic targets for patients. Methods: Based on the workflow of a cytokine signalling resource, CytokineLink, we developed previously, in this effort we built novel interaction networks using single-cell expression data from patients with ulcerative colitis (UC) and Crohn's disease (CD). We defined two meta-networks for each disease: a cell–cell communication network connected by cytokines; and a cytokine–cytokine interaction network depicting the potential ways in which cytokines can affect the activity of each other. Results: The rewiring of cell–cell and cytokine–cytokine interaction networks between healthy, non-inflamed and inflamed intestinal tissues in IBD was measured using the generated meta-networks. Cytokine-cytokine interaction networks revealed that in active UC, the Th1 cytokine IFNg and the chemokines CCL28 and CCL14 were central to cytokine-mediated communication networks. In CD, IL12B and IL13 formed the central cytokines in inflamed ileal tissues. Cell–cell interaction networks identified likely main cell types mediating the signalling of these key cytokines in non-inflamed and inflamed intestinal tissues: mast cells being the main source of IL13 in both IBD patients and healthy individuals. Conclusion: We generated interaction networks aimed at capturing the most prevalent cell–cell and cytokine–cytokine interactions using disease specific single-cell expression data. Using the generated interaction networks we identified the condition-specific rewiring of cytokine mediated signalling in IBD, and key cytokines that could be targeted for ameliorating inflammatory responses. The data can be used by the community as a platform for hypothesis-generation. Potential use cases are deconvoluting the complexities of cytokine signalling in IBD to reveal potential cytokine drug targets, or predicting the downstream effects of drugs on cytokine responses.